Tourism for Development : Tourism Diagnostic Toolkit - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
The Tourism Diagnostic Toolkit provides systematic guidance for identifying and assessing opportunities and constraints in the tourism ecosystem, as well as identifying potential points of entry for WBG interventions. The toolkit includes information on the WBG's current tourism offer and the tourism diagnostic process, a set of indicators and checklists for conducting secondary research. It also includes a process to assess the country's readiness for sustainable development of its tourism sector. This toolkit should be used in tandem with FCI's Tourism Theory of Change. The Tourism Diagnostic Toolkit is part of an evolving set of FCI tourism resources, which are available for project teams to use as part of their work on tourism projects.